A Simple and Efficient Method for Trifluoroacetylation of Arylamines Using Trifluoroacetic Acid and Triphosgene - Han, Ki-Jong; Kim, Misoo (Letters in Organic Chemistry, 2011)
A simple and efficient one-pot procedure for trifluoroacetylation of arylamines using trifluoroacetic acid and triphosgene is reported. A mixed trifluoroacetic anhydride generated in situ reacts with a variety of arylamines to give the corresponding trifluroacetamides in high yields.
Keywords: trifluoroacetamides